German public finances through the financial crisis - Blömmer, Maximilian Joseph; Dolls, Mathias; Fuest, Clemens; Löffler, Max; Peichl, Andreas (Mannheim, 2015)
"The German experience of the crisis was very different compared to those of most other countries in Europe. Germany was hit by a very strong shock which was relatively concentrated in the exporting, manufacturing industries. In addition, the German labour market was very resilient during the crisis due to earlier labour market reforms and policy instruments facilitating labour hoarding. As a consequence, public finances were only moderately affected and not many policy reforms had to be enacted. This chapter will present the German experience of the financial crisis. We start by presenting the macroeconomic situation and how the crisis unfolded in Germany, before focusing on the situation of public finances. Finally, we analyse the policy responses to the financial crisis."